2020
DOI: 10.14309/ctg.0000000000000235
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the Esophageal Microbiome and Tissue Gene Expression and Links to the Oral Microbiome: A Randomized Clinical Trial

Abstract: INTRODUCTION: Although the microbiome is altered in various esophageal diseases, there is no direct evidence for a link between the oral or esophageal microbiome and underlying esophageal tissue. Here, we aimed to address these gaps through use of an antimicrobial mouth rinse to modify the esophageal microbiome and tissue gene expression. METHODS: In this randomized controlled trial, patients scheduled to undergo endoscopy for clinical indications used chlorhexidine mou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…The bacterial microbiome is an emerging co-factor in esophageal health and disease (see recent reviews for more comprehensive discussion [41,46,47]). While the esophagus was long believed to be sterile, a growing body of evidence suggests that there is a stable esophageal bacterial microbiome that is heavily influenced by the oral microbiome [48][49][50]. In health, the esophageal microbiome primarily consists of 95 taxa belonging to six phyla, Firmicutes, Bacteroides, Actinobacteria, Proteobacteria, Fusobacteria, and Saccharibacteria phylum (also known as TM7) [51,52].…”
Section: The Bacterial Microbiome In Esophageal Health and Diseasementioning
confidence: 99%
“…The bacterial microbiome is an emerging co-factor in esophageal health and disease (see recent reviews for more comprehensive discussion [41,46,47]). While the esophagus was long believed to be sterile, a growing body of evidence suggests that there is a stable esophageal bacterial microbiome that is heavily influenced by the oral microbiome [48][49][50]. In health, the esophageal microbiome primarily consists of 95 taxa belonging to six phyla, Firmicutes, Bacteroides, Actinobacteria, Proteobacteria, Fusobacteria, and Saccharibacteria phylum (also known as TM7) [51,52].…”
Section: The Bacterial Microbiome In Esophageal Health and Diseasementioning
confidence: 99%
“…For example, this topic has been assessed in the context of the lung microbiome when distinguishing microbiota from bronchoalveolar lavage fluid and contemporaneous oral wash [27]. In a recent randomized controlled trial, the oral microbiome and esophageal microbiome were shown to be tightly linked as assessed by oral swabs and esophageal brushings that were sterilized at the beginning of the upper endoscopy [28]. This study found that intervention with chlorhexidine mouth rinse over 2 weeks caused significant alterations in the oral microbiome when compared to the untreated group (Wilcoxon rank-sum p = 0.013 for pairwise distances measured with weighted UniFrac), and this intervention also changed the expression of several genes associated with inflammation measured by RNAseq of esophageal tissue [28].…”
Section: Potential Role Of Esophageal Microbiome In Be and Eacmentioning
confidence: 99%
“…In a recent randomized controlled trial, the oral microbiome and esophageal microbiome were shown to be tightly linked as assessed by oral swabs and esophageal brushings that were sterilized at the beginning of the upper endoscopy [28]. This study found that intervention with chlorhexidine mouth rinse over 2 weeks caused significant alterations in the oral microbiome when compared to the untreated group (Wilcoxon rank-sum p = 0.013 for pairwise distances measured with weighted UniFrac), and this intervention also changed the expression of several genes associated with inflammation measured by RNAseq of esophageal tissue [28]. No study has yet fully revealed whether changes in the microbiome could relieve gastroesophageal reflux symptoms, or if BE metaplasia creates a different microenvironment that attracts different types of microbes compared to the normal esophagus [29]; thus, further investigation is warranted.…”
Section: Potential Role Of Esophageal Microbiome In Be and Eacmentioning
confidence: 99%
See 1 more Smart Citation
“…The esophageal microbiome is broadly similar to the oral microbiome, with an abundance of anaerobes and a high Firmicutes to Bacteroidetes ratio [ 1 , 2 ]. This link between the mouth and esophagus was demonstrated by a recent, randomized controlled trial of an antimicrobial mouth rinse, in which oral microbiome alterations were found to directly impact esophageal microbiome composition and cause marked changes in esophageal tissue gene expression [ 3 ]. In light of the oral–esophageal microbiome connection, esophageal microbiome changes associated with neoplasia may be reflected in the mouth, an easily accessible sampling site.…”
Section: Introductionmentioning
confidence: 99%